2019
DOI: 10.21873/cgp.20135
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Chloride Ion Channel Protein-1 Expression in Clear Cell Renal Cell Carcinoma

Abstract: Background/Aim: Chloride intracellular channel 1 (CLIC1) represents a promising target for personalized therapy. Our aim was to assess CLIC1 expression in clear cell renal cell carcinoma (cc RCC) and identify its possible prognostic role. Materials and Methods: Fifty cases of cc RCC were evaluated and selected for immunohistochemistry. CLIC1 expression was correlated with tumor grade, invasion and heterogeneity. Results: A total of 87.5% of the cases were CLIC1 positive, with either a homogeneous (31.42%) or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 37 publications
(48 reference statements)
2
20
0
Order By: Relevance
“…Previous research has shown that altered expression of particular genes may affect ESCC cell metastasis, invasion, apoptosis and proliferation [15][16][17] . Our results agree with the fact that carcinoma cell metastasis and invasion are closely associated with abnormal cell adhesion, endodermal cell division and nuclear division [18][19][20] . Extracellular matrix (ECM), is a critical component of the cancer cell niche, it can provide the tissue with the mechanical support and also mediate the cell-microenvironment interactions 21,22 .…”
Section: Discussionsupporting
confidence: 92%
“…Previous research has shown that altered expression of particular genes may affect ESCC cell metastasis, invasion, apoptosis and proliferation [15][16][17] . Our results agree with the fact that carcinoma cell metastasis and invasion are closely associated with abnormal cell adhesion, endodermal cell division and nuclear division [18][19][20] . Extracellular matrix (ECM), is a critical component of the cancer cell niche, it can provide the tissue with the mechanical support and also mediate the cell-microenvironment interactions 21,22 .…”
Section: Discussionsupporting
confidence: 92%
“…The cytoplasmic chloride ion channel protein-1 (CLIC1) is normally expressed in the glomerulus and epithelial cells of the kidney proximal tubules [129]. CLIC1 is overexpressed in many tumor types [130] and drives glioblastoma cell growth and proliferation [131]. In response to oxidative stimuli and malignant transformation, CLIC1 translocates from the cytoplasm to the cell membrane [132][133][134], where it functions as a selective chloride channel that affects cell cycle regulation, cell size, membrane potential, and cell proliferation/differentiation [130,135].…”
Section: Ion Channel Signalingmentioning
confidence: 99%
“…CLIC1 is overexpressed in many tumor types [130] and drives glioblastoma cell growth and proliferation [131]. In response to oxidative stimuli and malignant transformation, CLIC1 translocates from the cytoplasm to the cell membrane [132][133][134], where it functions as a selective chloride channel that affects cell cycle regulation, cell size, membrane potential, and cell proliferation/differentiation [130,135]. As expected, high CLIC1 expression has been found in 50 resected samples of human ccRCC in both malignant tissue and sites of intravascular invasion, with G3 tumors displaying the most heterogeneous CLIC1 distribution [130].…”
Section: Ion Channel Signalingmentioning
confidence: 99%
“…The chloride intracellular channel 1 (CLIC1) belongs to p64 family, which mainly exists in the nucleus, but also in the cytoplasm and cell membrane 11,12 . CLIC1, expressed in multiple tissues and organs, is highly conserved throughout evolution and its expression level varies little among different species.…”
Section: Introductionmentioning
confidence: 99%